Effect of Transplanting Date on Growth and Yield of Sweet Pepper (Capsicum annuum L.) under Open and Net House Environment at Rampur, Chitwan, Nepal - Lamsal, Ganesh; Shrestha, Arjun Kumar; Tripathi, Kalyani Mishra; Giri, Hom Nath (Nepalese Horticulture, 2022)
Sweet pepper, though a highly remunerative vegetable, environmental variability and inappropriate transplanting date have resulted low yield in Terai. Hence, to identify the suitable transplanting date under open and net house environment, a field research was conducted at Agriculture and Forestry University, Rampur, Nepal, from October 2018 to May 2019. A split-plot design was used with two factors and three replications. Main-factor comprised of growing environments (open field and net house) and sub-factor was transplanting dates (October 15, November 4, November 24 and December 14).The plant height (94.38 cm), leaf area (91.24 cm2), plant spread (55.22 cm) as well as fruit quality parameters like fruit length (8.72 cm), fruit girth (7.32 cm), fruit weight (63.07 g) and pericarp thickness (6.85 mm) were significantly higher under net house while these parameters were significantly lower in open field. Significantly greater marketable yield was observed under net house (20.08 t/ha) than open field (16.29 t/ha).The plant growth and yield parameters were significantly the best with early transplanting date (October 15) and the least with December 14. Interactive effect revealed that October 15 inside the net house performed the best in terms of yield (33.31 t/ha) and marketable yield (33.17 t/ha), while the poorest performance was recorded on December 14 under open field with a yield of 3.96 t/ha and marketable yield of 3.48 t/ha. Therefore, transplanting inside the net house as early as October 15 helps to maximize sweet pepper yield with better size marketable fruits.